CATION-PI ANALYSIS IN STAPHYLOCOCCUS AUREUS TOXINS – AN IN SILICO APPROACH - RAMADEVI MOHAN,; RAO SETHUMADHAVAN,; SUBHASHREE VENUGOPAL, (International Journal of Pharma and Bio Sciences, 2015)
Structures of proteins are maintained by various non-covalent interactions, including Cation-pi interaction. In this study, we have investigated those interactions responsible for maintaining structures in toxins produced by Staphylococcus aureus. Toxins are potent activators of the immune system that produce a variety of diseases in humans by direct binding of major histocompatibility complex (MHC) class II molecules on Antigen presenting cells and active T cells bearing a particular T-cell receptor beta chain variable (Vβ) domain. Considering its importance in clinical aspects, we analyzed the interactions in 24 different toxins of the bacterium by in silico with respect to structure, stability involving secondary structures, conservation scores, solvent accessibility and stabilization centers. Out of 24 toxins investigated, we found cation-pi interactions in 22 proteins and there is a preference of Lys over Arg in cationic residues and Tyr among pi residues. The least energy value of -109.65 kcal/mol of Toxic Shock Syndrome Toxin (PDB code 2QIL) revealed its greater stability. The residues involved in forming cation-pi interactions are found buried inside the protein and highly conserved. The analysis inferred that the interaction is found common and important for maintaining the protein structure, stability to deliver the toxicity and disease mechanism in host.